The Influence Of Past Traumatic Experience On The Personality Development Reflected At Nabila Sharma's Brutal: The Heartbreaking True Story Of A Little Girl's Stolen Innocence (2012) Memoir: A Psychoanalytic Approach - Miskatun, Sa'idah; , Dr. M. Thoyibi, M.S; , Titis Setyabudi, S.S. M. Hum (2014)
The major problem of this research is to describe how is the influence of past traumatic experience on the personality development reflected in Nabila Sharma's memoir. The object of the study is Brutal: the Heartbreaking True Story of a Little Girl's Stolen Innocence novel written by Nabila Sharma. The research consists of two objectives as follows: to describe the Nabila Sharma's novel based on the structural elements and to analyze the influence of past traumatic experience on the personality development reflected at the novel based on psychoanalytic approach. This study used qualitative research. There are two kinds of data source, namely: primary and secondary. The primary data source is the story of Nabila Sharma's novel and the secondary data sources such as website, dictionary, and some book related to the subject. The method of collecting data is library research by summarizing, paraphrasing, and documenting the data. In analyzing the data, the researcher applies descriptive analysis. The conclusions of the study are as follows. First, based on the structural analysis, it can be concluded that the author of the memoir delivered message that the violence of children must be stopped. Second, based on the psychoanalytic analysis it can be concluded that Nabila illustrated a psychological phenomenal in which the life of an individual is very much influenced by the past traumatic experience. She also criticizes practices of child molestation among Pakistani immigrants in England.